1992
DOI: 10.1104/pp.99.4.1400
|View full text |Cite
|
Sign up to set email alerts
|

Transport Interactions between Paraquat and Polyamines in Roots of Intact Maize Seedlings

Abstract: Interactions between absorption of paraquat and the polyamines putrescine, cadaverine, and spermine in roots of intact maize (Zea mays L. cv 3377 Pioneer) seedlings were examined. Concentrationdependent kinetics for paraquat and putrescine influx were similar and both kinetic curves could be resolved into a linear and a saturable component. The linear component was previously shown to represent cell wall/membrane binding. The saturable components for paraquat and putrescine uptake, which represent influx acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 19 publications
5
91
0
Order By: Relevance
“…Moreover, we demonstrated that natural variation in RMV1 defines PQ uptake in A. thaliana. These data support the hypothesis that PQ enters plant cells via a transport system that inherently functions in the transport of PAs, which have structural similarities to PQ (17). Our data imply that other transporters in addition to RMV1 may participate in PA uptake in Arabidopsis, suggesting the existence of diverse transport systems, which might serve to increase the repertoire of PAs that plants can absorb from the environment.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Moreover, we demonstrated that natural variation in RMV1 defines PQ uptake in A. thaliana. These data support the hypothesis that PQ enters plant cells via a transport system that inherently functions in the transport of PAs, which have structural similarities to PQ (17). Our data imply that other transporters in addition to RMV1 may participate in PA uptake in Arabidopsis, suggesting the existence of diverse transport systems, which might serve to increase the repertoire of PAs that plants can absorb from the environment.…”
Section: Resultssupporting
confidence: 73%
“…Kinetic analysis further indicated that RMV1 is capable of mediating PQ transport against a concentration gradient (Fig. 3F) (17). Moreover, the PQ uptake in the OX-C transgenic plants showed pH dependency (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putrescine is also a precursor of y-aminobutyrate (Flores, 1990), which may function as a signal molecule after stress in plants (Snedden et al, 1995(Snedden et al, ,1996. Putrescine may be involved in inhibiting paraquat uptake or the transport system, as found by Hart et al (1992) in an isolated root system. Because only putrescine levels were greatly enhanced, we only added putrescine exogenously to mimic this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…In animal tissues it has been shown that paraquat transport occurs by carriers that also function as carriers of other molecules such as polyamines (Rannels et al, 1989, Jóri et al, 2007. Hart et al (1992aHart et al ( 1992b demonstrated that paraquat movement across plasma membrane root epidermal and cortical maize cells has a concentration-dependent kinetic and that the herbicide binds to cell wall, and its transport is facilitated by a carrier that normally functions in the movement of molecules that has a similar chemical structure or similar charge distribution such us diamines like putrescine and cadaverine. Using maize protoplast showed that paraquat uptake has similar concentration-kinetic to that observed in intact cells and the accumulation inside cells increase in a timedependent manner and is saturated after 10 min, although 50% of uptake occurs during the first 10 s. The saturable K m for paraquat uptake in maize cells and protoplasts was determined at 90 µM and 132 µM respectively, similarly the K m in rat lung was 70 µM www.intechopen.com Herbicides -Properties, Synthesis and Control of Weeds 136 suggesting in both animal and vegetal tissues a carrier-mediated process (Rannels et al, 1985).…”
Section: Introductionmentioning
confidence: 99%